Self-access Learning :A General Review - Eltyeb Almukashfi, Dr. Lubab (Gezira Journal of Educational Sciences and Humanities, 2004)
The paper addresses both teachers of English as a foreign language and staff of the specialists departments at universities. It attempts to draw the attention to the importance of self-access learning as an excellent complement to classroom teaching. The paper begins with identifying the context and implications of self-instruction. Following that, the reasons that necessitate the application of self-access are clearly stated. The paper also points to the expected obstacles when introducing ‘self-access' in the educational system. Finally, it calls for a radical change in teaching and learning English, learners should be independent, initiators and creative. It is hoped that this paper will be of interest and service to both teachers of English and staff of the specialist departments since the general principles of self-instruction are universally applicable.